Interventions for promoting and optimizing breastfeeding practices: An overview of systematic review - Khatib, Mahalaqua Nazli; Gaidhane, Abhay; Upadhyay, Shilpa; Telrandhe, Shital; Saxena, Deepak; Simkhada, Padam Prasad; Sawleshwarkar, Shailendra; Quazi, Syed Zahiruddin (Frontiers in Public Health, 2023)
Background: Optimal breastfeeding (BF) practices are essential for child survival and proper growth and development. The purpose of this overview is to evaluate the effectiveness of different interventions for promoting and optimizing breastfeeding. Methods: We included systematic reviews (SRs) (including trials from Low-Income (LICs) and Low Middle-Income countries (LMICs)) that have evaluated the effect of various interventions for promoting and optimizing breastfeeding and excluded non-systematic reviews and SRs based on observational studies. We followed the standard methodology as suggested by the Cochrane Handbook for Systematic Reviews of Interventions. Result: We identified and screened 1002 Cochrane SRs and included six SRs in this overview. Included SRs reported only two of the primary outcomes, early initiation of breastfeeding (EIBF) and/or exclusive breastfeeding (EBF). None of the included SRs reported continued BF up to two years of age. The results were evaluated using two major comparison groups: BF intervention against routine care and one type of BF intervention versus other types of BF intervention. Overall results from included SRs showed that there were improvements in the rates of EIBF and EBF among women who received BF intervention such as BF education sessions and support compared to those women who received only standard care. However, BF intervention via mobile devices showed no improvements. In Target Client Communication (TCC) via mobile devices intervention group, no significant improvements were reported in BF practices, and also the reported evidence was of very low certainty. Conclusion: Community Based Intervention Packages (CBIP) delivered to pregnant and reproductive-age women during their antenatal care (ANC) and/or Postnatal care (PNC) periods by Ancillary Nurse-Midwives reported the highest improvement in EIBF compared to women who received standard care. However, insufficient evidence was reported to suggest that BF intervention showed improvements in EBF in both the comparison groups. This overview highlighted the gaps in primary research regarding the uncertainty about the settings such as LICs or LMICs, lack of evidence from LMICs, and also identified gaps in the availability of reliable up-to-date SRs on the effects of several BF interventions to promote and optimize practices.